MIMO antenna with built‐in circular shaped isolator for sub‐6 GHz 5G applications. Issue 8 (1st April 2018) - Saxena, S.; Kanaujia, B.K.; Dwari, S.; Kumar, S.; Tiwari, R.
Abstract : A four‐port MIMO antenna design focused on the sub‐6 GHz fifth generation wireless communication application is presented. The design does not need any other decoupling structure for achieving isolation between multiple ports. A combination of four single wideband antenna units results in the formation of a circular‐shaped metallic disc in the ground plane of the proposed antenna. This disc acts as a pool of current with 180° phase difference leading to isolation between various ports. Diversity performance of the antenna is shown with the help of an envelope correlation coefficient using both S‐parameter and far‐field data. The radiation pattern of the proposed antenna has four lobes in four quadrants for proper reception of signals from different directions. A prototype of the designed antenna is fabricated and measured successfully.